Estimating the thermal effect in gPhoneX observations - NOVÁK, Adam; JANÁK, Juraj (Contributions to Geophysics and Geodesy, 2022)
Stationary relative gravimeters are used in variety of applications, mainly due to their high sampling rate which is more suitable for study of certain geodynamic effects than absolute gravimeters. Study of weak signals is almost exclusively in the domain of superconducting gravimeters, as they possess the highest accuracy and stability of all types of relative gravimeters. Possible alternative to superconducting gravimeters are portable earth tide metal spring gravimeters. Zero-length spring gravimeters (e.g. LCR instruments) are usually considered to be the most accurate mechanical spring gravimeters. However, compared to superconducting instruments they remain too unstable for long-term gravity monitoring. Main reason supporting this statement is related to instrument's sensitivity to temperature changes and temperature induced tilts. Gravity observations from the gPhoneX #108 gravimeter stationed at Hurbanovo gravimetric observatory were tested in order to confirm the correlation between the observed gravity changes and ambient temperature changes and provide a solution for correcting the gPhone data for influence of the ambient temperature changes. Paper also aims to serve as a guide for other operators to estimate a parameters required for the calculation of ambient temperature correction.